Executive compensation in business groups: Evidence from China - Guilong Cai; Guojian Zheng (China Journal of Accounting Research, 2016)
This paper examines executive compensation in the subsidiaries of business groups in China. Analyzing a sample of China business groups (the so-called 'XiZu JiTuan' in Chinese) from 2003 to 2012, we find convincing evidence of the use of Relative Performance Evaluation (RPE) in the executive compensation of the subsidiaries of business groups. Specifically, when the change in performance of one subsidiary is lower than that of the other subsidiaries, the change in its executive compensation is significantly lower. Further, when the business group is private and the level of marketization is high, the subsidiary's executive compensation is more likely to be influenced by the performance of the other subsidiaries. This research improves our understanding of the decision mechanisms of executive compensation in business groups and enriches the literature on executive compensation and business groups.
Keywords: G32; G34; J31; L22; 650; Business group; Executive compensation; RPE; China